Abordagens sintéticas para a obtenção dos alcaloides tetra-hidroquinolínicos cuspareina e galipinina e avaliação antibacteriana de alguns intermediários frente a cepas de Staphylococcus aureus - Raquel Geralda Isidorio (2015)
Alkaloids are often found in plants and have great structural and chemical variety, they are classified from her structure or amino acid from which they originated. Some alkaloids are called specials and among them, are the tetrahydroquinolines. The tetrahydroquinoline alkaloids have several biological activities so has aroused synthetic keen interest. Cuspareine and galipinine are two alkaloids isolated from a Rutaceae, Galipea officinalis Hancock, a typical plant of the South American continent. Several synthetic routes have been developed to obtain these alkaloids not extinguished, however, new possibilities. It was proposed like the synthetic route to these alkaloids, work with common intermediate, the benzylic halide, the derivate 3 and a reagent Grignard. Coupling the Grignard reagent with the intermediate 3, would result in cuspareine or galipinine alkaloids, accord with the Grignard reagent synthetized. The synthesis route from the Grignard was not successful, because it was observed the formation of byproducts of polimerization Grignard benzyl in all methods adopted. The byproduct has been isolated and characterized. The proposed route was abandoned and proceeded to retry from the witting reaction of with aldehyde tetrahydroquinoline and phosphonium salt. There indicative coupling with consequent formation of the derivative 27, but the alkaloids they were not synthetized. The biological tests was divided into two stages, where in the first stage was carried the screening of derivates able of inhibiting bacterial growth. Eleven derivatives were tested and six showed halo formation, which was measured in millimeters, indicating inhibition of the growth of the bacteria Staphylococcus aureus. The six derivatives were submitted to the second stage of the biological testing, determination of minimum inhibitory concentration. In the two stages was tested the strains S. aureus bacteria 3008, 4125 and 4158 isolated from bovine affected by bovine mastitis. Attention is drawn to the fact that the S. aureus bacteria isolated from bovine mastitis already has resistance to treatment by antibiotics and chemotherapeutics. Bovine mastitis is a recurring and difficult to combat disease. The S. aureus bacteria it can also affect the human triggering various diseases of hard combat. The toxins released by these pathogens are responsible for toxic epidermal necrosis (scalded skin syndrome) and toxic shock syndrome. They are also likely to cause foodborne infections, staphylococcal bronchopneumonia (usually elderly), bacteremia, meningitis, bone infections, septic arthritis, bone graft infections.